9(2X+1)平方=16(X-3)平方
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 18:37:06
9(2X+1)平方=16(X-3)平方9(2X+1)平方=16(X-3)平方9(2X+1)平方=16(X-3)平方9(2X+1)平方=16(X-3)平方3²(2X+1)²=4
9(2X+1)平方=16(X-3)平方
9(2X+1)平方=16(X-3)平方
9(2X+1)平方=16(X-3)平方
9(2X+1)平方=16(X-3)平方
3²(2X+1)²=4²(X-3)²
[3×(2X+1)]²=[4×(X-3)]²
(6X+3)²=(4X-12)²
两边开方得:
6X+3=±(4X-12)
一、当6X+3=4X-12时:
2x=-15
x=-7.5
二、当6X+3=-4X+12时:
10x=9
x=0.9
9(2X+1)平方=16(X-3)平方
3(2x+1)=±4(x-3)
6x+3=4x-12 或 6x+3=-4x+12
分别解得:
2x=-15
x=-7.5
或10x=9
x=0.9
-7.5或0.9
9(2X+1)平方=16(X-3)平方
(x平方-1)平方=9 (2X平方-3)平方=4
9X平方;+4=(3X平方-1)(2X平方+2)
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
因式分解,过程1、(x平方+y平方)(x平方+y平方-4)+4 2、(9a平方+4b平方)平方 3、x+y=-1,x-y=-3,x平方-y平方=
解方程 196x平方-1=0 4x平方+12x+9=81 x平方-7x-1=0 2x平方+3x=3 x平方-2x+1=25...196x平方-1=04x平方+12x+9=81x平方-7x-1=02x平方+3x=3x平方-2x+1=25x(2x-5)=4x-10x平方+5x+7=3x+111-8x+16x平方=2-8x
方程2/X平方+X+3/X平方-X=4/X平方-1
9x平方=(X-1)平方
比较2x平方+4x+9与(x+3)平方+(x-1)平方的大小
(2x平方-3x+1)平方=22x平方-33x +1解方程
X平方+3x+1=0 求:2x平方+X平方 分之 2
(2-x)平方=16 4(x+1)平方-25=0 x平方-2x+1=3
a4次方-2a平方b平方-8b4次方x平方-4y平方+4y-1x4次方-6x3次方+9x平方-16(x平方-3)平方-4x平方
(x平方-1)的平方-(2x+2)平方 (x平方+x)(x平方+x-2)-3(x平方-1)的平方-(2x+2)平方(x平方+x)(x平方+x-2)-3分解因式
1:2分之3X的平方-{-2分之1X平方}+{-2X平方}.2:{9X平方-3+2X}+{-X-5+2X平方}
16x平方+8x+2=( )平方+1RT
(x-1)平方=9(2x+1)平方
(x+2)的平方=9(x-1)的平方